2018
DOI: 10.3390/nu10030351
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Fractures in Dermatitis Herpetiformis Compared to Coeliac Disease

Abstract: Dermatitis herpetiformis (DH) is a cutaneous manifestation of coeliac disease. Increased bone fracture risk is known to associate with coeliac disease, but this has been only scantly studied in DH. In this study, self-reported fractures and fracture-associated factors in DH were investigated and compared to coeliac disease. Altogether, 222 DH patients and 129 coeliac disease-suffering controls were enrolled in this study. The Disease Related Questionnaire and the Gastrointestinal Symptom Rating Scale and Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…In our previous study investigating self-reported fractures, the lifetime bone fracture risk was found to be equal between patients with DH and coeliac disease, except that females with coeliac disease had a higher fracture risk after being diagnosed compared to females with DH. 26 In the current study, the hospital-treated fractures overall were increased in the coeliac disease cohort compared to the DH cohort, which is in line with our previous finding. However, females aged 80-89 in the DH cohort had an increased hip fracture incidence compared to the comparable coeliac disease cohort.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study investigating self-reported fractures, the lifetime bone fracture risk was found to be equal between patients with DH and coeliac disease, except that females with coeliac disease had a higher fracture risk after being diagnosed compared to females with DH. 26 In the current study, the hospital-treated fractures overall were increased in the coeliac disease cohort compared to the DH cohort, which is in line with our previous finding. However, females aged 80-89 in the DH cohort had an increased hip fracture incidence compared to the comparable coeliac disease cohort.…”
Section: Discussionsupporting
confidence: 92%
“…The intestinal type of CD is more frequently observed in the paediatric population and children younger than three years of age. It is characterised by diarrhoea, loss of appetite, abdominal distention and failure to thrive [35] . Children and adults may complain of diarrhoea, bloating, constipation, abdominal pain, or weight loss.…”
Section: Symptoms Of Celiac Diseasementioning
confidence: 99%
“…A mineralizáció elégtelensége miatt megfigyelhetők a kórképre jellemző fogzománceltérések [23]. Mind a coeliakia, mind a dermatitis herpetiformis tünetei között gyakori a csontok ásványianyag-denzitásának csökkenése, ami mindkét betegség esetén az átlagpopulációnál nagyobb arányban hajlamosít csonttörésekre [44,45].…”
Section: A Dermatitis Herpetiformishoz Társuló Betegségekunclassified